2011
DOI: 10.2967/jnumed.111.089185
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 4 Radiolabeled Antagonists for Serotonin 5-HT7 Receptor Neuroimaging: Toward the First PET Radiotracer

Abstract: Brain serotonin 7 (5-hydroxytryptamine 7, or 5-HT 7 ) is the most recently identified serotonin receptor. It is involved in mood disorders and is studied as a target for antidepressants. Because no radioligand has yet been successfully used to study this receptor by PET neuroimaging, the objective of the present study was to develop a 5-HT 7 18 F-labeled radiotracer. Methods: Four structural analogs of SB269970, a specific 5-HT 7 receptor antagonist, were synthesized. The nitro precursors of these analogs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…Among these, [ 18 F]2FP3 (K i = 8.4 nM, Fig. 11) and [ 18 F]4FP3 (K i = 14 nM, Figure 11) show specific binding in vitro in brain sections of rats [175]. In vivo studies in cats show excellent brain uptake, regional distribution and specific binding for [ 18 F]2FP3 [176].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, [ 18 F]2FP3 (K i = 8.4 nM, Fig. 11) and [ 18 F]4FP3 (K i = 14 nM, Figure 11) show specific binding in vitro in brain sections of rats [175]. In vivo studies in cats show excellent brain uptake, regional distribution and specific binding for [ 18 F]2FP3 [176].…”
Section: Introductionmentioning
confidence: 99%
“…The mismatch between regional distribution volumes of [ 18 F]2FP3 and the in vitro autoradiography outcomes supports that [ 18 F]2FP3 has off‐target binding. We can only speculate in the nature of the potential in vivo off‐target binding as affinity was only tested for the 5‐HT 7 , 5‐HT 1A , and 5‐HT 6 receptors and with apparent affinity for the two latter targets . Similarly, low affinity for the D 2 (790nM), D 3 (631nM), and 5‐HT 6 (3.21μM) receptors was identified of the closely related compound 12 in the publication by Lovell et al The blocking effect obtained in these studies contrasts the results obtained in cats, where the TACs strongly indicated a blocking effect after preadministration of SB‐269970 (5 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, low affinity for the D 2 (790nM), D 3 (631nM), and 5‐HT 6 (3.21μM) receptors was identified of the closely related compound 12 in the publication by Lovell et al The blocking effect obtained in these studies contrasts the results obtained in cats, where the TACs strongly indicated a blocking effect after preadministration of SB‐269970 (5 mg/kg). However, since the arterial input function was not determined in these experiments, the binding before and after pretreatment with SB‐269970 was not quantified …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5-HT 7 R antagonist (R)-3-(2-(2-(4-methylpiperidin-1-yl)ethyl)pyrrolidine-1-sulfonyl) phenol (SB-269970) has been used as a lead structure for discovering 18 F-labeled radioligands. 18 F-1-{2-[(2S)-1-(phenylsulfonyl) pyrrolidin-2-yl]ethyl}piperidin-4-yl 4-fluorobenzoate and 1-(2-{(2R)-1-[(2-18 F-fluorophenyl)sulfonyl]pyrrolidin-2-yl}ethyl)-4-methylpiperidine ( 18 F-2FP3) were evaluated ex vivo in rats and in vivo in cats (9,10). However, no input function was obtained while evaluating 18 F-2FP3.…”
mentioning
confidence: 99%